The Relationship Between Anxiety Level with the Onset of Acne Vulgaris in Medical Faculty of Universitas Sumatera Utara 2016 – 2018 - Salsabila, Vanny; Hazlianda, Cut Putri (Talenta Publisher, 2022)
Acne vulgaris (AV) is a chronic inflammation of the follicle pilosebaceous induced by Propionibacterium acnes. Anxious circumstances increase the androgen hormones. This increases the production of sebum and the proliferation then activates Propionibacterium acnes, resulting in AV. To find out the relationship between levels of anxiety and the onset of AV to the Faculty of Medicine, Universitas Sumatera Utara (FK USU) 2016 – 2018 conducted observational research with cross sectional design. This research samples as many as 66 students of FK USU Group 2016 – 2018 and using stratified random sampling method. The result of anxiety level of FK USU students indicates that there are mild anxiety (92.4%) moderate anxiety (6.1%) and severe anxiety (1.5%). The AV event of FK USU students indicates that there are mild acne (51.5%) moderate acne (40.9%) severe acne (6.1%) and normal results (1.5%). With the chi square test there is a significant link between the level of anxiety and the onset of the vulgaris (p = 0.026). There is a significant relationship between the levels of anxiety with the onset of AV on student of FK USU 2016-2018.